Characteristics and controlling factors of alpine grassland vegetation patch patterns on the central Qinghai-Tibetan plateau - Wei Zhang (Elsevier, 2021)
Vegetation patch patterns, which are used as indicators of state, functionality, and catastrophic changes in the arid ecosystem, have received much attention. However, little is known about the controlling factors and indicators that underlie vegetation patch patterns in the alpine grassland ecosystem. Here, we firstly studied characteristics of vegetation patch patterns with aerial photography by using an unmanned aerial vehicle and evaluated the vegetation patch-size distribution with power law (PL) and truncated power law (TPL) models on the central part of the Qinghai-Tibetan Plateau (QTP). We then investigated the effects of environmental factors and biotic disturbances on vegetation patch patterns. The results showed that (1) there were four typical vegetation patch patterns, i.e. spot, stripe, sheet, and uniform patterns; (2) soil water content and air temperature were major environmental factors affecting vegetation patch patterns; (3) biotic disturbance of plateau pika (Ochotona curzoniae) affected vegetation patch patterns by changing the number, area, and connectivity of vegetation patches; and (4) vegetation patch-size distribution parameters were significantly related to soil hydrothermal variables (P < 0.01). We concluded that the development of alpine vegetation patch patterns was controlled by soil hydrothermal conditions and plateau pika’s disturbance. We also proposed that γ (TPL-PL) (difference between absolute values of slopes of TPL and PL curve fits) could serve as an effective indicator for monitoring alpine grassland conditions, and preventing patchiness was a critical task for the alpine ecosystem management and restoration.